2017
DOI: 10.1590/2177-6709.22.4.053-060.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPP-ACP paste with and without CO2 laser irradiation on demineralized enamel microhardness and bracket shear bond strength

Abstract: Introduction: Many patients seeking orthodontic treatment already have incipient enamel lesions and should be placed under preventive treatments. The aim of this in vitro study was to evaluate the effect of CPP-ACP paste and CO2 laser irradiation on demineralized enamel microhardness and shear bond strength of orthodontic brackets. Methods: Eighty caries-free human premolars were subjected to a demineralization challenge using Streptococcus mutans. After demineralization, the samples were randomly divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
4
22
1
2
Order By: Relevance
“…Many other studies have also used this test to measure the remineralization changes. 26,27,31,34 The findings of the present study were in contrast with those of Heravi et al indicating that the use of the erbium laser alone and in combination with CPP-ACPF was not effective in the treatment of WSLs. 26 These differing results may be due to the difference in various parameters of lasers used such as pulse energy, pulse duration, energy density, radiation time, and use of or not use of air or water for cooling during laser irradiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Many other studies have also used this test to measure the remineralization changes. 26,27,31,34 The findings of the present study were in contrast with those of Heravi et al indicating that the use of the erbium laser alone and in combination with CPP-ACPF was not effective in the treatment of WSLs. 26 These differing results may be due to the difference in various parameters of lasers used such as pulse energy, pulse duration, energy density, radiation time, and use of or not use of air or water for cooling during laser irradiation.…”
Section: Discussioncontrasting
confidence: 99%
“…51 Despite the higher microhardness values obtained in the laser groups, the differences were not significant. As a result, the synergistic effect of the laser with the remineralizing agents was not evident in our findings, which is similar to the findings from the study by Farhadian et al 52 Melting and recrystallization of the enamel surface may explain higher microhardness values and also the higher intensity of HA peaks for the laser groups. Contrary to our findings, Khamverdi et al and Niyazi et al showed a synergistic effect of the CO 2 laser with CPP-ACP on improving the enamel microhardness, which confirms the facilitating role of lasers in the penetration of remineralizing agents into deeper layers of HA.…”
Section: Discussionsupporting
confidence: 88%
“…Lazer kullanımının mineralizasyonu hızlandırdığı, aynı zamanda kristal büyümesini de kontrol edebileceği düşünülmektedir. 67,69 Topikal florür tedavisi ile birleştirilen lazer ışınlamasının, florür alımını arttıran ve minenin çözünme oranını tek başına lazer veya florür uygulamasına kıyasla önemli ölçüde azaltan sinerjistik bir etki yarattığı gösteren çalışmalar olduğu gibi lazer uygulamasının belirgin remineralizasyon etkisinin olmadığı ve florun etkisini arttırmadığını da bulgulayan çalışmalar da mevcuttur. [70][71][72] Ayrıca çeşitli lazer türlerinin CPP-ACP içeren remineralizasyon materyalleri ile birlikte kullanımı ile ilgili araştırmalar da yapılmıştır.…”
Section: Kitosanunclassified
“…Bazı araştırmacılar lazerin demineralize mine yüzeyindeki CPP-ACP'nin remineralizasyon etkisini arttırdığını bildirse de bazı çalışma sonuçlarına göre lazer ve CCP-ACP'nin birlikte kullanılmasının sinerjistik bir remineralizasyon etkisinin olmadığı gözlemlenmiştir. 69,73 Lazerlerin tek başına ya da remineralizasyon materyalleri ile birlikte kullanımını değerlendiren birçok çalışma yapılmış olsa da sonuçlar çelişkilidir ve etkinliğinin kanıtlanabilmesi için daha fazla klinik araştırma yapılmasına ihtiyaç vardır.…”
Section: Kitosanunclassified